Eksperimental Kecepatan Elektroda Las Busur Listrik Menggunakan Sliding Adaptive Two Axis Pada Sambungan Mild Steel ASTM A36 - Radinal Fernandes; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to determine the ideal welding speed in Shield Metal Arc Welding with 1G position on ASTM A36 mild steel welding using a Sliding adaptive Two Axis With Speed Control system. Welding is done automatically and the welding speed is adjusted using the Speed Control. For each welding process, the welding speed can be adjusted according to the welding conditions, such as to a different current or polarity. The output of the Sliding Adaptive Two Axis With Speed Control system is in the form of speed data in mm / s stored in data log. The results of welding are carried out three tests, namely the Visual Test, Penetrant Test, and Tensile Test, the test is carried out to determine which specimen is the best. Experiments were carried out using an Esab AWS E6013 electrode with a diameter of 3.2 mm and using an AC (Alternating Current) with three variations of current strength. From the results of experiments carried out at a current strength of 90 A, the ideal welding speed is 2.88 mm / s with a tensile strength value of 434.00 MPa, for a current strength of 105 A it is obtained 3.56 mm / s with a tensile strength value of 434.0 MPa and for a current strength of 120 A obtained an ideal welding speed of 4.23 mm / s with a tensile strength value of 487.65 MPa. Keywords: Sliding adaptive Two Axis With Speed Control, alternating current, data log, 1G